Experimental Reconstruction of a Nineteenth Century Lower Limb Prosthetic Peg Leg – The Box Leg - Charlotte Waller-Cotterhill (EXARC Journal)
Scientific attempts to understand early prosthesis manufacturing techniques are rare. The academic research of artificial limbs has been limited to the historical analysis of documentary sources. This area still remains a fairly under-researched topic even under the more recent developments of disability studies (Childress, 1985). There may be many reasons for this; the organic materials used in manufacturing limbs such as wood and leather, mean few prostheses survive archaeologically in situ, and disability was until more recent times hidden or not spoken of (Sweet, 2016). Our understanding of the early artificial limb manufacturing industry, has been based primarily on drawings, patent applications and rudimentary manufacturing methodologies. However, that all societies (past and present) follow a single technological trajectory just at different rates of progress would be an inaccurate assumption (Pfaffenberger, 1992). Therefore, the employment of experimental methods can aid the exploration of technological questions surrounding consumer networks, use and discard patterns, craft specialisation and workforce requirements.